Searching for Peace in Central and South Asia : (Lynne Rienner Publishers, 2002)
Continuing a widely acclaimed series, Searching for Peace in Central and South Asia provides critical background information, up-to-date surveys of the violent conflicts in Afghanistan, Bangladesh, the Ferghana Valley, India, Nepal, Pakistan, Sri Lanka, and Tajikistan, and a directory of more than 150 organizations working in the field of conflict prevention and peacebuilding in the region. The book includes detailed, objective descriptions of ongoing activities, as well as assessments of future prospects for conflict resolution, focusing on efforts to make civil society an integral part of any peace process